The Effectiveness of Photodynamic Therapy as An Adjunct to Mechanical Debridement in Peri-Implantitis Treatment - Sosiawan, Agung; Azhar, Imam Safari; Dhywinanda, Devin Elysia; Jordana, Jesslyn; Salim, Jennifer Fiona; Nugraha, Alexander Patera (Faculty of Dental Medicine Universitas Airlangga, 2022)
Background: Peri-implantitis is one of many factors that can cause implant failure, with common cases ranging from 1%-47% and the highest incidence ranging from 10.7%- 47.2%. Mechanical debridement (MD) is currently the standard for peri-implantitis treatment. However, MD has limitations in the removal of infected tissue. Moreover, the rough texture of the implant's surface and bacteria adhesion and colonization increases the difficulty in performing MD. To overcome these limitations, adjunct therapy is needed to increase peri-implantitis treatment effectiveness. One of those adjunct therapies, photodynamic therapy (PDT), is used to destroy bacterial cells and significantly reduce inflammatory cell infiltration around the implant. Purpose: To describe the effectiveness of PDT as an adjunct therapy to MD in periimplantitis treatment through narrative review. Review: PDT is effective in reducing the number of bacteria, plaque index (PI), bleeding on probing (BOP), probing depth (PD), crestal bone loss (CBL), and excessive proinflammatory cytokines (IL-6, IL-1β, TNF-α) in patients. However, the effectiveness of PDT can be influenced by several factors, including patients' conditions, such as diabetes and smoking habits, types of photosensitizers used, and exposure time. Conclusion: PDT is an effective adjunctive therapy to MD in peri-implantitis treatment since it can improve clinical parameter values, significantly reduce P. gingivalis, and decrease proinflammatory cytokines.